Moderasi Good Corporate Governance Terhadap Pengaruh Risiko Perusahaan Pada Manajemen Laba - Pradnyani, Ida Ayu Devi Candra; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2019)
The risk of a company is a condition for the possibilities that cause a firm's performance to be lower than what the company expects because of a certain uncertain condition in the future. In this study the risk of the company is proxied by leverage. Leverage is the ratio of debt usage by firms used as funding for corporate expenses, whose financing comes from debt use. This study took a sample based on non-probability sampling method with purposive sampling technique at manufacturing companies in Indonesia Stock Exchange in the range of 2014-2016. The number of samples obtained is 204 observations. In this research, the data analysis technique used is simple regression test and Moderated Regression Analysis (MRA) test. Based on the results of this research analysis found that corporate risk with leverage proxy has a positive effect on earnings management. GCG is able to moderate the effect of corporate risk with leverage proxy on earnings management. Keywords: earnings management, corporate risk, leverage, GCG, audit committ ee.